Effects of Nitride on the Tribological Properties of the Low Carbon Alloy Steel - Yuh-Ping Chang; Jin-Chi Wang; Jeng-Haur Horng; Li-Ming Chu; Yih-Chyun Hwang (Advances in Materials Science and Engineering)
The technology of composite heat treatment is used popularly for low friction and wear resistance of drive elements. A large number of papers about the heat treatment technology had been proposed. Especially, the nitride treatment has been used widely for the purpose of wear resistance and low friction in the industry. Therefore, the self-developed vertical ball/disk friction tester with the measurement system was used to study the effects of nitride on the tribological properties of the low carbon alloy steel—SCM415— in this study. The experiments were conducted under dry and severe wear conditions. The variations of friction coefficient and surface magnetization were simultaneously recorded during dynamic friction process. After each test, the microstructures of the wear particles were observed and analyzed under a SEM, and the depth of wear track is measured by means of a surface tester. According to the experimental results, the wear resistance of the specimens with carburizing-nitride is significantly larger than the case of nitride-carburizing. Moreover, the surface magnetization was especially larger for the case of nitride-carburizing. As a result, the wear particles always stay in the interfaces and the wear mechanism becomes complex. Therefore, it is necessary to put nitride after carburizing for the composite heat treatments.